2019
DOI: 10.1088/1742-6596/1339/1/012115
|View full text |Cite
|
Sign up to set email alerts
|

Media Development on the Concept Sentence Learning Model based Android for Students with Hearing Impairment

Abstract: This study aims to find out development of android based learning media that adopts the Concept Sentence model for students with hearing impairment, so that their learning outcomes, especially in understanding a social science’s learning materials would increase. The subjects of the study were 30 students from one of the special schools for students with hearing impairment in Surakarta City. The present study was conducted using a research and development method. The data were collected using a questionnaire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Appropriate learning media, especially those related to Physical Education learning for the students with hearing impairment, is relevant to one of the Sustainable Development Goals (SDGs) goals, namely quality education and equality for disabilities (Mirasandi, et al, 2019). The results of a preliminary study, conducted by researchers on Google Play store and Google Scholar, had not found Physical Education learning applications for students with hearing impairment in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate learning media, especially those related to Physical Education learning for the students with hearing impairment, is relevant to one of the Sustainable Development Goals (SDGs) goals, namely quality education and equality for disabilities (Mirasandi, et al, 2019). The results of a preliminary study, conducted by researchers on Google Play store and Google Scholar, had not found Physical Education learning applications for students with hearing impairment in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…4's description is to use simple texts related to public buildings (al-mabani al-"ammah) that are close to the daily lives of students, by paying attention to social functions, text structures, and correct linguistic elements and in context. Indicators of achieving competency in this learning are: 47 writing the words / phrases that result from reading text identification, writing words / phrases then forming one sentence according to the theme with the appropriate sentence structure on the Creative Board media for sentence development, demonstrating the results of writing by raising the Creative Board media, so that it can be corrected by the teacher and recommunicating the writing. Through the use of media for the use of Creative Board media for sentence development, students can express and use simple transactional interaction written texts related to speech acts of public facilities / school buildings, by paying attention to social functions, text structures, and correct linguistic elements according to the context with a sense of curiosity, responsibility, discipline during the learning process.…”
Section: School Pb Soedirman 1 Bekasimentioning
confidence: 99%